2013
DOI: 10.1155/2013/545948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 Flow Rate on the Pinang Frond‐Based Activated Carbon for Methylene Blue Removal

Abstract: Activated carbons are regularly used the treatment of dye wastewater. They can be produced from various organics materials having high level of carbon content. In this study, a novel Pinang frond activated carbon (PFAC) was produced at various CO2 flow rates in the range of 150–600 mL/min at activation temperature of 800°C for 3 hours. The optimum PFAC sample is found on CO2 flow rate of 300 mL/min which gives the highest BET surface area and pore volume of 958 m2/g and 0.5469 mL/g, respectively. This sample s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The sample produced was stored in air-tight container for further characterization and adsorption studies. The detail of preparation was described in the [14].…”
Section: Preparation and Characterization Of Activated Carbonmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample produced was stored in air-tight container for further characterization and adsorption studies. The detail of preparation was described in the [14].…”
Section: Preparation and Characterization Of Activated Carbonmentioning
confidence: 99%
“…The surface area was determined using the Brunauer-Emmet-Teller (BET) equation which is the most usual standard procedure used when characterizing an activated carbon. It was found that the BET surface area, average pore diameter, and pore volume of the PF-AC were 958.23 m 2 /g, 2.32 nm, and 0.5469 cm 3 /g, respectively [14]. to prepare the concentration of 1 g/L dye solution.…”
Section: Preparation and Characterization Of Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно [1][2][3], что повышение температуры процесса сопровождается меньшим порообразованием и большим обгаром (окислением по поверхности) материала. Указывается, что на протекание процесса (порообразование или окисление по поверхности) влияет расход окислителя [4] и природа окисляемого материала [5][6][7][8][9]. Отмечается [10], что при использовании воздуха (кислорода) процесс следует проводить при более низких температурах.…”
Section: Introductionunclassified
“…Therefore, other alternative precursors which are inexpensive and abundantly available for activated carbon production have been investigated. From the literature, oil palm stone [4], pinang frond [5], banana stalk [6], bamboo species [7], coffee husk [8], date pits [9], oil palm shell [10] and Parkinsoniaaculeatea wood [11] have all been used to prepare activated carbon.…”
Section: Introductionmentioning
confidence: 99%